Genotyping and macrolide-resistant mutation of Bordetella pertussis in East and South-East Asia - Koide, Kentaro; Yao, ShuMan; Chiang, Chuen‑Sheue; Thuy, Phung Thi Bich; Nga, Do Thi Thuy; Huong, Do Thu; Dien, Tran Minh; Vichit, Ork; Vutthikol, Yong; Sovannara, Siphan; Samnang, Chham; Takayama, Ikuyo; et al. (Journal of Global Antimicrobial Resistance, 2022)
•Molecular surveillance of macrolide-resistant Bordetella pertussis (MRBP) was performed in East and Southeast Asia.•MBRP was detected in Vietnam, Cambodia, Taiwan, and Japan.•Most MRBP had the same MT104 and MT195 genotypes as Chinese MRBP.•The first MRBP isolates from Taiwan belonged to the MT104 cluster of Chinese MRBP. Macrolide-resistant Bordetella pertussis (MRBP) has been emerging and prevailing in mainland China since 2011. In this study, we aimed to investigate the genotype and macrolide resistance of circulating B. pertussis in East and Southeast Asia using genetic analyses. A total of 302 DNA extracts from clinical specimens and isolates from 2010 to 2020 were analyzed: 145 from Vietnam, 76 from Cambodia, 48 from Taiwan, and 33 from Japan. Genotypes were determined by multilocus variable-number tandem-repeat analysis (MLVA). Macrolide-resistant A2047G mutation in B. pertussis 23S rRNA was investigated using the duplex Cycleave real-time polymerase chain reaction (PCR) assay. Whole-genome sequencing was performed on two MRBP isolates that were identified for the first time in Taiwan. Overall, 286 DNA extracts (95%) generated a complete MLVA genotype and 283 DNA extracts (94%) yielded a complete result for the A2047G mutation analysis. The A2047G mutation was detected in 18 DNA extracts: fourteen from Vietnam, one from Cambodia, two from Taiwan, and one from Japan. Most of them (78%) showed the genotypes MT104 and MT195, which have previously been reported in Chinese MRBP isolates. Further, the Taiwanese MRBP isolates were classified into the MT104 clade of Chinese MRBP isolates. After MRBP emerged and spread in mainland China, it may have spread to East and Southeast Asia in the 2010s. Continued surveillance targeting the A2047G mutation of MRBP is needed to prevent further spread of this emerging pathogen.